Proteomics analysis of aging proteins - Morvan, Marine (Univerzita Pardubice, 2023)
The analysis and characterization of aging and archaeological proteins are among the latest challenges in analytical chemistry. In the first part of this dissertation thesis, aging proteins were studied using LC-MS. The effects of aging on protein sequences, including amino acid racemization, post-translational modifications, and protein degradation, were studied. Subsequently, a chiral separation method was developer to determine the amino acid enantiomer rates. In the second part of this dissertation thesis, archaeological proteins were studied using nanoLC-MS. Proteomics, called paleoproteomics in this case, was developed as an alternative method for osteoarchaeology and genomics. Based on two sex-dependent forms of amelogenin protein preserved in teeth, both biological sexes were distinguished by nanoLC-MS because of differences in their protein sequences. The developed proteomic approach was designed to be minimally-invasive. This was confirmed by scanning the teeth before and after amelogenin extraction using both scanning electron microscope and micro-computer tomography.
Proteomická analýza stárnoucích proteinů
Keywords: amelogenin; aminokyseliny; chirální separace; degradace proteinů; kolagen; LC-MS; paleoproteomika; posttranslační modifikace; proteomika stárnutí; aging proteomics; amelogenin; amino acids; chiral separation; collagen; LC-MS; paleoproteomics; post-translational modifications; protein degradation